Pelatihan Sistem Cloud Computing Menggunakan Layanan Dropbox Bagi Mahasiswa Baru - Saputra, Gilang; Prasetyo, Muhammad Rasyid; Maulana, Farrel Rizqullah Ilham; Ikhsan, Teguh Pribadi (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2025)
Cloud computing is a combination of computer technology and internet-based development. Cloud computing uses the term "cloud", or cloud, to describe the internet, which is often depicted on computer network diagrams. Cloud computing capacity is an information technology service that can be accessed via the internet without knowing the infrastructure behind it. This opens up the possibility of accessing and using technology more efficiently and flexibly. The development of information technology, especially cloud computing, has had a significant impact in various fields, including education. Cloud computing changes the way information technology is distributed and accessed, providing opportunities for educational institutions to access data and educational resources more efficiently and flexibly. It also helps educational institutions to focus more on core educational processes without having to manage technology infrastructure directly. Teaching about cloud computing is becoming increasingly important. Because through an introduction to the basic concepts, types, benefits and practical applications of cloud computing, students can understand the importance of this technology in the modern world. Thus, teaching and training measures such as those described in this study are expected to help increase the understanding and application of cloud computing among students, preparing them for the challenges and opportunities in the ever-evolving digital era.